A Systematic Review of Respiratory Sinus Arrhythmia in Romantic Relationships. Issue 2 (16th March 2021) - Han, Sohyun C.; Baucom, Brian; Timmons, Adela C.; Margolin, Gayla
Abstract : Respiratory sinus arrhythmia (RSA), an index of the parasympathetic nervous system, has recently gained attention as a physiological component of regulatory processes, social connectedness, and health. Within the context of romantic relationships, studies have operationalized and conceptualized RSA in disparate ways, obscuring a clear pattern of findings. This systematic review synthesizes the rapidly developing literature and clarifies the role of RSA in romantic relationships. We evaluate support for three conceptual hypotheses: (1) resting baseline RSA is associated with better quality relationships; (2) phasic RSA is reflective of changes in threat and connection during couple interactions; and (3) physiological linkage in RSA between romantic partners relates to positive or negative relationship functioning depending on the nature of the linkage (e.g., in‐phase vs. antiphase). We identified 26 empirical studies that tested associations between RSA and an index of romantic relationships (i.e., relationship satisfaction). Our findings show that higher RSA is not uniformly "good" for relationships. Higher resting baseline RSA was contemporaneously associated with better quality relationships, yet higher baseline RSA was also unexpectedly associated with relationship violence. Short‐term decreases in RSA were found during relationship conflict, though the opposite—phasic increases in RSA during positive romantic partner interactions—was not found due to mixed empirical support. As expected, evidence for RSA linkage was found, though the connection between linkage and relationship functioning depends on the context in which it was measured. We discuss methodological limitations and directions for future research. Resumen: La arritmia sinusal respiratoria (ASR), un índice del sistema nervioso parasimpático, ha sido objeto de atención recientemente como componente fisiológico de los procesos reguladores, la conexión social y la salud. Dentro del contexto de las relaciones amorosas, los estudios han operacionalizado y conceptualizado la ASR de diversas maneras, ocultando un patrón claro de signos. Este análisis sistemático sintetiza la bibliografía que se está desarrollando rápidamente y aclara el papel que desempeña la ASR en las relaciones amorosas. Evaluamos el respaldo de tres hipótesis conceptuales: (1) una ASR de reposo en el momento basal está asociada con relaciones de mejor calidad; (2) la ASR refleja cambios en la amenaza y la conexión durante las interacciones de la pareja; y (3) la asociación fisiológica en la ASR entre los integrantes de la pareja se relaciona con el funcionamiento positivo o negativo de la relación según la índole de la asociación (p. ej.: en fase frente a contrafase ). Identificamos 26 estudios empíricos que evaluaron las asociaciones entre la ASR y un índice de las relaciones amorosas (p. ej.: la satisfacción con la relación). Nuestros resultados indican que una ASR más alta no es uniformemente "buena" para las relaciones. Una ASR de reposo más alta en el momento basal estuvo asociada contemporáneamente con relaciones de mejor calidad, sin embargo, una ASR más alta en el momento basal también estuvo asociada inesperadamente con la violencia de pareja. Se encontraron disminuciones de la ASR a corto plazo durante el conflicto en las relaciones, aunque no se encontró lo opuesto —aumentos fásicos en la ASR durante las interacciones positivas de los integrantes de la pareja— debido a un respaldo empírico ambivalente. Como se esperaba, se encontraron indicios de una asociación de la ASR, aunque la conexión entre la asociación y el funcionamiento de la relación depende del contexto en el cual se midió. Comentamos las limitaciones metodológicas y damos indicaciones para investigaciones futuras. 摘要: 呼吸窦性心律失常(RSA)是副交感神经系统的一个指标，近期的研究中作为调节过程、社会联系和健康的一个生理组成部分受到关注。针对恋爱关系情境中进行的研究，对RSA的操作和概念化的研究方式有所差别，它们无法提供清晰的研究结果的模式。本文综合了快速增加的文献作了系统性的综述，明晰了RSA在爱情关系中的作用。我们评估了对三个概念性假设的支持。(1)静止时基线RSA与更好的关系质量相关；(2)阶段性RSA反映了伴侣互动过程中不良的兆头和伴侣连接关系方面的变化；(3)恋爱伴侣之间RSA的生理联动与积极或消极的关系功能有关，这取决于联动的性质(例如，同相联动与反相联动)。我们找出26项实证研究，这些研究测试了RSA与恋爱关系指数（即关系满意度）之间的关联。我们的研究结果表明，更高的RSA并不都是"好的"关系。较高的静止时基线RSA与较好的关系质量同时相关，然而较高的基线RSA也出乎意料地与关系暴力相关。在关系冲突期间，研究虽发现了短期的RSA下降，但在良好的恋爱伴侣互动中，出现反相联动的RSA增加的现象却尚未发现，这是由于有多种实证的支持。正如预期的那样，发现了RSA联动的证据，尽管这种生理联动和恋爱关系功能之间的联系取决于测量它的具体场景。本文也讨论了研究方法方面的局限性和未来的研究方向。